Pengembangan Media Pembelajaran Berbasis Game Edukasi Pada MatPel IPA Tematik Kebersihan Lingkungan - Reni Widyastuti; Listia Sari Puspita (LPPM Universitas Bina Sarana Informatika, 2020)
Game is one of the interactive multimedia products which is developing rapidly in the world, including Indonesia. Educational games can be used as an alternative interactive learning media that has the goal of supporting the learning process with the concept of